MENGEMBANGKAN KEMAMPUAN KOGNITIF DALAM MENGENAL KONSEP BILANGAN 1 – 10 MELALUI MEDIA TELUR ANGKA PADA ANAK USIA 3 – 4 TAHUN - Mukhlish Safitri; Intan Prastihastari Wijaya; Dema Yulianto (incrementapedia, 2020)
Cognitive ability to recognize the concept of numbers is very important to be introduced early on, so children are accustomed to easily solving simple problems related to numbers. The problem found by researchers is that children have difficulty when asked to numerate objects, numerically order numbers, and connect images of objects with numbers according to the amount. In an effort to address this problem, the educator introduces new media, namely the number egg media made from used materials and designed as attractive as possible so that students were motivated to learn. This study aims to determine whether there is cognitive development in recognizing the concept of numbers 1-10 in children aged 3-4 years in the Playgroup Al-hikmah Kweden Karangrejo Ngasem District Kediri Regency between before and after the action. The research method used is classroom action research conducted in three cycles. This research involved subjects of 3-4 years old children totaling 18 students. The analysis technique in this research is quantitative descriptive technique by comparing learning completeness between the time before and after the action. The results obtained in the first cycle of 50%, and in the second cycle of 63.8%, while in the third cycle of 81.9%. From the results of the study it can be concluded that through the egg media numbers can develop cognitive abilities in recognizing the concept of numbers 1-10 in children aged 3-4 years.